Of mice and men – environmental temperature, body temperature, and treatment of obesity. Issue 12 (10th May 2018) - Reitman, Marc L.
Abstract : Mice are widely used for exploring obesity physiology and treatment. However, thermal biology is different between small and large mammals. In this Review, we discuss how the effect of environmental temperature must be understood to ensure applicability of mouse experiments to human obesity. At ambient environmental temperature ( 22 °C), over one‐third of energy expenditure in mice is devoted to maintaining core body temperature, largely by brown adipose tissue. To conserve this energy, mice can enter a regulated hypothermia, while humans do not. Since humans expend little or no energy specifically to keep warm, mice studied at thermoneutrality ( 30 °C) may be a better model for human energy homeostasis. Studies indicate that environmental temperature also affects the efficacy of drugs that increase energy expenditure. In mice, dinitrophenol, a protonophore, and CL316243, a β3‐adrenergic agonist, both increase metabolic rate at thermoneutrality, but only CL316243 increases it at 22 °C. Furthermore, mice housed at thermoneutrality may become more obese than mice at 22 °C. Thus, we discuss the importance of studying mice at both thermoneutrality and at lower temperatures in obesity research. Abstract :